Electrochemical behaviour of copper in potassium thiocyanate solution : II. Analysis of potentiostatic current transients - Figueroa, M. G. (1987)
The kinetics of passivity and pitting corrosion of copper in borate-boric acid buffer containing potassium thiocyanate is studied at 25°C by means of potentiostatic transients recorded at different constant potential values. Three different potential regions are distinguished. Region I, as the applied potential is increased, implies the successive formation of cuprous thiocyanate, cuprous and cupric oxide. This corresponds to the formation of a composite anodic layer. Region II extends from the potential of the third anodic voltammetric peak up to the breakdown potential. Region III involves the breakdown of the passive layer caused by thiocyanate ions, and the formation of different copper salts in the pits. The kinetics of the various stages is discussed in terms of an extension of the nucleation and growth mechanism following an approach which was earlier applied for explaining the initiation and growth of pitting corrosion of metals.